2016
DOI: 10.4236/aim.2016.614103
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Ubiquity of Ascomycetes Filamentous Fungi in Relation to Their Economic and Medical Importance

Abstract: Filamentous fungi are found in different habitats in the environment including, air, water and soil. This group of fungi contains organisms from different classes under the sub-phylum Pezizomycotina. They occur in mixtures such that you find many genera of filamentous fungi dominating a particular habitat or substrate. The wide distribution of filamentous fungi has resulted in it being used for different purposes. This review aims to analyse the different genera of fungi species referred to as filamentous fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 95 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Penicillium fungi are ubiquitous in soil (Egbuta et al, 2016) and are considered a key group in P cycling (Harvey et al, 2009;Richardson et al, 2011). In part this is due to their ability to solubilize inorganic P through the release of organic anions (Richardson et al, 2011), although with considerable differences between species (Wakelin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Penicillium fungi are ubiquitous in soil (Egbuta et al, 2016) and are considered a key group in P cycling (Harvey et al, 2009;Richardson et al, 2011). In part this is due to their ability to solubilize inorganic P through the release of organic anions (Richardson et al, 2011), although with considerable differences between species (Wakelin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to its ability to survive in conditions of low humidity, extreme temperatures, and low pH since the growth of phosphate-solubilizing microorganisms is influenced by soil acidity (Fatmala et al, 2015). Besides, the fungus A. terreus tends to also increase the growth of Ceriops tagal seedlings (Egbuta et al, 2016). Furthermore, Mehmood et al (2018) and Radhakrishnan et al (2015) reported that fungi in the genus Fusarium have great potential to dissolve phosphate and produce IAA.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…A. terreus and F. oxysporum belong to the same division namely Ascomycota. Egbuta et al (2016), stated that the most researched and utilized kingdom fungus is Ascomycota.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…Genus Emericella (E.) includes more than thirty species and is named after the sexual phase (teleomorph) of this fungal strain, which ranges from saprobes to pathogenic or endophytic organisms on living host organism [23]. It forms white cleistothecia surrounded by Hülle cells and produces purple ascospores.…”
Section: Introductionmentioning
confidence: 99%